Pre-service teachers’ ways of understanding, observing, and supporting self-regulated learning - Latva-aho, Jenni; Näykki, Piia; Pyykkönen, Saara; Laitinen-Väänänen, Sirpa; Hirsto, Laura; Veermans, Marjaana (Elsevier, 2025)
This study explores pre-service teachers' (PSTs') ways of understanding, observing, and supporting self-regulated learning (SRL). The implementation of an open-ended questionnaire (N = 118) was followed by a qualitative analysis based on Zimmerman's SRL framework. The PSTs reflected on their understanding of the phases of SRL: forethought, performance, and reflection. The PSTs demonstrated a theoretical understanding of SRL but a weaker understanding of how to observe and support students' SRL skills and their development. The findings have practical implications for teacher education and teachers' professional development.